2014
DOI: 10.1016/j.epidem.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential impact of mass praziquantel administration for HIV prevention in Schistosoma haematobium high-risk communities

Abstract: Genital infection with Schistosoma haematobium is prevalent in sub-Saharan Africa. Epidemiological studies have observed that genital schistosomiasis is associated with an increased odd of HIV infection among women. We used mathematical modeling to explore the potential impact of mass preventive chemotherapy against schistosomiasis on HIV transmission in three sub-Saharan Africa countries: Angola, Kenya, and Zambia. We developed a model of female genital schistosomiasis (FGS) and HIV transmission dynamics, fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…To estimate posterior distributions for the unknown epidemiological parameters—probability of tsetse bite on humans ( β VH ), transmission probability from tsetse to humans ( β H ), treatment seeking rate of stage II patients ( ζ ) and transmission probability from tsetse to NHA ( β L )—we used a Bayesian melding method [ 23 , 24 ] to calibrate the model to prevalence data for stage I and stage II HAT cases in Boffa East Mainland in 2008, as well as Trypanosomiasis prevalence among tsetse and the NHA reservoir [ 12 , 21 ]. Given that there was no active screening or vector control in Boffa between 2000 and 2008, we assumed an equilibrium prevalence prior to 2008.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate posterior distributions for the unknown epidemiological parameters—probability of tsetse bite on humans ( β VH ), transmission probability from tsetse to humans ( β H ), treatment seeking rate of stage II patients ( ζ ) and transmission probability from tsetse to NHA ( β L )—we used a Bayesian melding method [ 23 , 24 ] to calibrate the model to prevalence data for stage I and stage II HAT cases in Boffa East Mainland in 2008, as well as Trypanosomiasis prevalence among tsetse and the NHA reservoir [ 12 , 21 ]. Given that there was no active screening or vector control in Boffa between 2000 and 2008, we assumed an equilibrium prevalence prior to 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Luckily, urogenital schistosomiasis is a treatable condition. Studies have shown genital lesions to regress after treatment with praziquantel [ 2 , 14 , 15 ]. Some protection against sexually transmitted infections (STIs) and HIV infection may also be achieved when infected individuals are treated (untreated urogenital schistosomiasis may result in various tissue lesions that can be easily infected by other bacteria and/or viruses).…”
Section: Introductionmentioning
confidence: 99%
“…Other operational research needs for praziquantel include evaluation of the efficiency and safety when used in conjunction with drugs for other neglected tropical diseases in integrated MDAs. In addition, with the recognition that schistosomiasis may increase risk of infection with malaria or HIV [17,18], the benefits of treating schistosomiasis on reducing the transmission or manifestations of these and other coinfecting agents should be considered.…”
mentioning
confidence: 99%